Evaluación de la calidad higiénica y sanitaria en carne de cerdo expendida en un mercado de Loja. - Zhingre Calva, Paúl Alexander (2023)
Pork meat is one of the most consumed foods at national level; however, inefficient ndling at any stage of the food chain can lead to contamination and microbial prevalence. Therefore, the objective of the present research work is to determine the microbiological quality of pork, sold in a market in Loja. The research had a cross-sectional observational design in which 24 samples of pork were collected from the spending sites located within a market in Loja. The presence of Escherichia coli, Salmonella spp. and Staphylococcus aureus through cultures and obtained by biochemical tests, additional colony-forming units per milliliter (ufc/ml) for mesophilic aerobes were counted according to the INEN 1338 regulations. The presence of Escherichia coli and Staphylococcus aureus was found in 8.33%, Salmonella spp. in 12.5% and mesophilic aerobes in values greater than 1.0 x 107 cfu/ml. In conclusion, the raw pork meat from the Loja market has bacteria and a count higher than what is allowed according to the food sanitation regulations in force in the country. It is recommended to carry out a traceability study to identify the origin of meat contamination. Key words: Microbiological cultures, Salmonella, Escherichia, Staphylococcus, Mesophilic aerobes.